Clinical characteristics and early mortality of patients undergoing coronary artery bypass grafting compared to percutaneous coronary intervention: Insights from the Australasian Society of Cardiac and Thoracic Surgeons (ASCTS) and the Melbourne Interventional Group (MIG) Registries - Yan, B.; Clark, D.; Buxton, B.; Ajani, A.; Smith, J.; Duffy, S.; Shardey, G.; Skillington, P.; Farouque, O.; Yii, M.; Yap, C.; Andrianopoulos, N.; et al. (Elsevier, 2009)
Objectives: Controversy continues over the optimal revascularisation strategy for patients with multi-vessel coronary artery disease. Clinical characteristics, risk profile, and mortality of patients undergoing coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) are thought to differ but there are limited contemporary comparative data. Methods: We compared clinical characteristics, in-hospital and 30-day mortality of 3841 consecutive patients undergoing isolated CABG and 4417 undergoing PCI. Independent predictors of 30-day mortality were determined by multiple logistic regression analysis. Results: CABG patients were older (p < 0.01). The CABG group had a higher incidence of diabetes, heart failure, left ventricular ejection fraction <45%, multi-vessel coronary artery, peripheral vascular and cerebro-vascular disease (all p < 0.01). Patients undergoing PCI had a higher incidence of recent myocardial infarction (MI) as the indication for revascularisation (p < 0.01). In-hospital and 30-day mortality was 1.8% and 1.7% in the CABG group, and 1.4% and 1.8% in the PCI group, respectively. Independent predictors of 30-day mortality after CABG were age (odds ratio 1.1 per year, 95% confidence interval 1.0-1.1), cardiogenic shock (4.10, 1.7-10.5) and previous CABG (6.6, 2.4-17.7). Predictors after PCI were diabetes (2.7, 1.4-5.1), female gender (3.0, 1.6-5.5), renal failure (3.2, 1.2-8.0), MI < 24 h (4.0, 2.2-7.6), left main intervention (5.4, 1.0-27.7), heart failure (6.0, 2.6-14.0) and cardiogenic shock (11.7, 5.4-25.2). Conclusions: In contemporary clinical practice, CABG is preferred in patients with multi-vessel coronary and associated non-coronary vascular disease, while PCI is the dominant strategy for acute MI. Despite this, in-hospital and 30-day mortality rates were similar. Predictors of early mortality after CABG differ to those of PCI. © 2008 Australasian Society of Cardiac and Thoracic Surgeons and the Cardiac Society of Australia and New Zealand.